Students’ Critical Thinking Skills in Learning through Gamification - Christian Hans; Yuliyanto Sabat; Siti Aisyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In the era of rapid modernization, the education sector is required to continuously adapt to technological developments, particularly in addressing the learning characteristics of Alpha Generation students who are highly familiar with digital technology and games. This study aims to explore the use of gamification as a teaching strategy to support the learning process and enhance students’ critical thinking skills. The research employed a qualitative method by selecting participants who were directly involved in gamified learning activities. Data were collected through interviews and classroom observations using structured interview instruments and observation notes to obtain in-depth and meaningful information. The collected data were analyzed qualitatively to identify patterns related to student engagement and critical thinking development. The findings reveal that game-based learning, specifically through the use of the Undercover game, positively influences the teaching process by increasing student engagement, analytical thinking, problem-solving abilities, and decision-making skills. Students were actively involved in analyzing information, evaluating alternatives, and collaborating with peers during the learning activities. The discussion indicates that gamification aligns well with the learning preferences of Alpha Generation students and creates an interactive learning environment that supports higher-order thinking skills. In conclusion, gamification can be considered an effective instructional approach for fostering critical thinking skills and improving learning outcomes in contemporary educational contexts.